2020
DOI: 10.1186/s43093-020-00038-5
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between real earnings management and crash risk of stock price during uncertainty? An evidence from family-owned firms in an emerging economy

Abstract: This research work intends to analyze the association between real earnings manipulation and stock price crash. Further, we also analyze the spillover outcome of the crash as a result of applying real earnings management. It is hypothesized that there is a positive and statistically significant association between real activities manipulation and crash risk. It is also assumed that this spillover outcome is more noticeable during uncertainty. By applying data of family firms for the time period 2005–2018, empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…This is a topic that has not been previously studied, and it has been found that in the years in which the stock market crashes occur and in the years shortly before and after them, the great majority of accounting deception begins. As commented for the first result obtained (the relationship between the scandal and the stock market crash), when a stock market crash occurs, the economy begins to deteriorate, which has a negative effect on many companies, which may encourage them to engage in accounting deception (Fatima et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is a topic that has not been previously studied, and it has been found that in the years in which the stock market crashes occur and in the years shortly before and after them, the great majority of accounting deception begins. As commented for the first result obtained (the relationship between the scandal and the stock market crash), when a stock market crash occurs, the economy begins to deteriorate, which has a negative effect on many companies, which may encourage them to engage in accounting deception (Fatima et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Dai et al (2019) reached the same conclusion in a study focused exclusively on Chinese companies. The same can be said of Fatima et al (2020) in relation to companies in Pakistan.…”
Section: Relationship Between Stock Market Crashes and Accounting Dec...mentioning
confidence: 90%
“…On the other hand, concentrated ownership can bring the entrenchment effect and lead to a higher conflict of minority-majority shareholders. Some studies find the entrenchment effect in the family firms that lead to higher earnings management behavior (Alhebri and Al-Duais, 2020;Fatima et al, 2020;Martin et al, 2017;Di Meo et al, 2017;Yang, 2010). Other studies also show the insignificant role of the family to reduce minority-majority shareholders and fail to mitigate earnings management behavior, such as Vieira (2016), who does not find a significant effect of family firms on earnings management or Tai (2017), who find that family directors tend to engage more in accrual earnings management than REM one.…”
Section: Family Firmsmentioning
confidence: 99%
“…, 2018). Also, the market environments of such countries are more involved in earnings management practices (Fatima et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, emerging or developing nations play a crucial role because the majority of firms in these countries are governed mainly by shareholders with majority shareholdings (Masud et al, 2018). Also, the market environments of such countries are more involved in earnings management practices (Fatima et al, 2020). Furthermore, unlike other countries, for the high transparency of the standards, the listed firms need to disclose the ownership of the firms (Mishra, 2021); thus, these countries are the ideal place for monitoring the role of ownership structure in alleviating opportunistic managerial behavior that is detrimental for investors.…”
Section: Introductionmentioning
confidence: 99%